Preface - Eger, Markus; Cardona-Rivera, Rogelio Enrique (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2023)
The 19th AAAI conference on Artificial Intelligence and Interactive Digital Entertainmentwas held at the University of Utah, in Salt Lake City, Utah, USA.